'The politicisation of transatlantic trade in Europe: Explaining inconsistent preferences regarding free trade and the TTIP - Aleksandra Sojka; Jorge Díaz-Lanchas; Frederico Steinberg (London School of Economics and Political Science (LSE), European Institute, 2020)
The Transatlantic Trade and Investment Partnership (TTIP) generated an unprecedented public contestation across Europe. In this paper, we focus on the sources of such backlash in European public opinion. Previous studies of this issue have analysed opinions on free trade and the specific agreement separately. However, not accounting for their correlated character could lead to biased conclusions about their determinants. To address this, we apply an innovative empirical approach and construct a set of bivariate probit models to calculate joint probabilities for the different configurations of support and opposition. We validate that attitudes toward free trade and the TTIP have similar but not identical foundations. Inconsistent preferences are rooted in individual values, EU attitudes, and political cues, as well as treaty partner heuristics. Our innovative empirical approach offers an improved understanding of trade attitudes within EU's multilevel context.
Keywords: 330; trade liberalisation; free trade; public opinion; trade agreements; TTIP